Cyclic variations of gonad development of an air-breathing fish, Channa striata in the lentic and lotic environments. Issue 1 (December 2016) - Al Mahmud, Nasim; Rahman, Hassan; Mostakim, Golam; Khan, Mohd.; Shahjahan, Md.; Lucky, Nahid; Islam, M.
Abstract The study was conducted to know the cyclic changes in gonadal maturation and to investigate the developmental stages of oocytes and testicular germ cells of an air-breathing fish, Channa striata . Fish were sampled monthly from lentic and lotic environments of three geographical locations of Bangladesh from December to November and the histological analysis of their gonad was done to evaluate the objectives. The highest mean GSI was 5.95 ± 0.20 for female in July and 0.14 ± 0.01 for male also in July showing that the gonadal development reached its peak during this month. The highest mean oocyte diameter was 1257.50 ± 24.17 μm observed in July implying that the oocyte reached maturity in this month. Histological study of ovary revealed the evidence of early yolk granule stage and late yolk granule stage from April to July. In case of male four stages of spermatogenesis were distinguished and spermatozoa were highly abundant in June and July. So the monthly pooled values of GSI and the analysis of gonadal histology indicated that the peak breeding season ofC. striata occurred in July in the lentic and lotic environments. Samples collected from lentic and lotic habitats are suggestive of no difference in the development of the gonad. The results of the present study will be useful for selective breeding programme, conservation and sustainable fishery management ofC. striata in its natural habitat.